INDIKATOR KUALITAS AUDIT: PERSEPSI AUDITOR INTERNAL PEMERINTAH MENGENAI FAKTOR-FAKTOR PERSONAL - ROCHMATUL LESTARI, NOVIA; VENUSITA, LINTANG (Jurnal Akuntansi AKUNESA, 2018)
The objective of this research is to observe Audit Quality in terms of auditor?s independence, integrity, professional competence, professional skepticism, and objectivity. This research uses 34 samples that consist of active auditors who work in Badan Pengawasan Keuangan dan Pembangunan (BPKP) as the government internal auditor. By using Partial Least Square (PLS), the result shows that integrity, professional competence and professional skepticism have significant impacts on audit quality but partially, independence and objectivity has no impact on Audit Quality. This shows that although the measurement for Audit Quality is broad and complex, the auditor personality still become the main role in order to determine the quality of audit. Keyword: Audit Quality, Personal Factors, BPKP.